Rabies surveillance in the United States evaluation of rabies virus variants - Dyer, J.; Blanton, J. D.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
During 2011, 49 states and Puerto Rico reported 6,031 rabid animals representing a 1.9% decrease from the 6,153 rabid animals reported in 2010. Relative contributions by the major animal groups were as follows: 1,981 raccoons (32.8%), 1,627 skunks (27.0%), 1,380 bats (22.9%), 427 foxes (7.1%), 303 cats (5.0%), 65 cattle (1.1%), and 70 dogs (1.2%). Compared to 2010, a significant increase was reported among rabid skunks. Canine rabies virus transmission has been eliminated in the United States since 2004 and monitoring the rabies virus variant associated with rabid domestic animals is critical. We evaluated rabies diagnostic submission data for the US from 2008-2011 for reported rabid dogs, cats and coyotes. A total of 1,546 rabid cats, dogs and coyotes were reported, with rabies virus variants characterized in 35%. Cats comprised the majority of rabid animals not characterized. No canine rabies virus variants were reported. Most rabid domestic animals were infected with the rabies virus variant circulating in the predominant mesocarnivore reservoir from the geographic area of submission. However, isolated cases associated with bat rabies virus variants were reported. These findings highlight the need for enhanced surveillance to monitor the circulation of rabies virus variants in local carnivore populations to determine emergence of new rabies virus variants. State health departments may not test suspect rabid animals unless a human exposure occurs. Moreover, variant typing is not performed on all samples though CDC provides rabies virus characterization, if requested. The public health implications of host shifts and potential spillover of rabies virus variants from wildlife to domestic animals reinforces the need for additional laboratory diagnostics.